Design and Development of Traffic Light and IR Camera Computer Network; a Tool for Infrastructural Planning and Revenue Generation - Umukoro Edafewhuotu; Alebu Ohimai; Olugotun Olubu (European Scientific Journal, ESJ, 2018)
A traffic light is a device that gives the right of way to any road user. The device is design with three visible colours made up of the Red, Yellow and Green light. It is used to control the movement of vehicles entry or leaving a junction of a town or cities. The red colour light indicates danger or stop movement. The yellow (amber) colour indicates get ready to start or stop movement. The green light indicates crossing the intersection without danger. The infrared camera (IR) is a light emitting diode (LEDs) which can video an image in an extreme low or absence of light condition. The IR camera when installed on a traffic light will capture every vehicle image, colour and the registration number of every vehicle that is given the right of way across an intersection in various locations. The captured data can be stored in a software drive (SD-card) or the hard-disk of the computer. The traffic light and IR camera are interface with a computer network system for visible and data retrieving for further programming processing. This system when installed can be used for infrastructural planning and revenue generation for the Government. It can also be used to prevent road accident and monitor the incessant knapping of the citizen. It serves as a tool for moral discipline for road user when defaulters are persecuted and charge to pay fine. The system will eliminate manual system of controlling traffic and embarrassment caused when there is traffic jam. The system is cheap and easy to install.